Higher dose of palonosetron versus lower dose of palonosetron plus droperidol to prevent postoperative nausea and vomiting after eye enucleation and orbital hydroxyapatite implant surgery: a randomized, double-blind trial - Hu X; Tan F; Gong L (Dove Medical Press, 2017)
Xiao Hu, Fang Tan, Lan Gong Department of Anesthesiology, The Eye, Ear, Nose and Throat Hospital of Fudan University, Shanghai Medical College of Fudan University, Shanghai, China Objective: Postoperative nausea and vomiting (PONV) is commonly observed after eye enucleation and orbital hydroxyapatite implant surgery. This prospective, randomized, double-blind trial was conducted to investigate the hypothesis that compared with monotherapy using a higher dose of palonosetron, using a lower dose of palonosetron in combination with droperidol could reduce the incidence of PONV and achieve similar prophylaxis against PONV after the aforementioned surgery.Patients and methods: A total of 129 patients who were in the American Society of Anesthesiologists Classes I and II, aged between 18 and 70 years, and scheduled for eye enucleation and orbital hydroxyapatite implant surgery, were enrolled in this study. They were randomized into three groups: Group P2.5 (2.5 µg/kg palonosetron), Group P7.5 (7.5 µg/kg palonosetron), and Group P+D (2.5 µg/kg palonosetron and 15 µg/kg droperidol). Patients received the different antiemetic regimens intravenously 5 min before surgery. The severity of nausea and vomiting and the complete response (CR) rate during a 72-h postoperative period were assessed.Results: All patients completed the trial. The nausea score of Group P2.5 was significantly higher than those of the other two groups at 0–4 h and 24–48 h (P<0.05). Vomiting scores among all groups were similar during all intervals (P>0.05). Compared with Group P2.5, the CR rate was significantly improved at all intervals in Group P+D, except at 4–72 h, and was also elevated at 24–72 h in Group P7.5 (P<0.05). Fewer patients in Group P2.5 did not experience any nausea or vomiting throughout the study (49%) compared with those in Group P7.5 (67%) and Group P+D (81%; P<0.01).Conclusion: Combining low-dose palonosetron with droperidol potentiated prophylaxis for PONV and achieved a similar prophylactic effect as that with a higher dose of palonosetron. Keywords: eye enucleation, orbital hydroxyapatite implant, palonosetron, PONV